SIRT2 Inhibition Results in Meiotic Arrest, Mitochondrial Dysfunction, and Disturbance of Redox Homeostasis during Bovine Oocyte Maturation - Xu, Dejun; Wu, Lin; Jiang, Xiaohan; Yang, Li; Cheng, Jianyong; Chen, Huali; Hua, Rongmao; Geng, Guoxia; Yang, Lulu; Li, Qingwang (International journal of molecular sciences, 2019)
SIRT2, a member of the sirtuin family, has been recently shown to exert important effects on mitosis and/or metabolism. However, its roles in oocyte maturation have not been fully clarified. In this study, SIRT2, located in the cytoplasm and nucleus, was found in abundance in the meiotic stage, and its expression gradually decreased until the blastocyst stage. Treatment with SIRT2 inhibitors resulted in the prevention of oocyte maturation and the formation of poor-quality oocytes. By performing confocal scanning and quantitative analysis, the results showed that SIRT2 inhibition induced prominent defects in spindle/chromosome morphology, and led to the hyperacetylation of α-tubulin and H4K16. In particular, SIRT2 inhibition impeded cytoplasmic maturation by disturbing the normal distribution of cortical granules, endoplasmic reticulum, and mitochondria during oocyte meiosis. Meanwhile, exposure to SirReal2 led to elevated intracellular reactive oxygen species (ROS) accumulation, low ATP production, and reduced mitochondrial membrane potential in oocytes. Further analysis revealed that SIRT2 inhibition modulated mitochondrial biogenesis and dynamics via the downregulation of TFAM and Mfn2, and the upregulation of DRP1. Mechanistically, SIRT2 inhibition blocked the nuclear translocation of FoxO3a by increasing FoxO3a acetylation, thereby downregulating the expression of FoxO3a-dependent antioxidant genes SOD2 and Cat. These results provide insights into the potential mechanisms by which SIRT2-dependent deacetylation activity exerts its effects on oocyte quality.